Arthroscopic suture bridge rotator cuff repair: functional outcome, repair integrity, and preoperative factors related to postoperative outcome. Issue 2 (2nd April 2016) - Rimmke, Nathan; Maerz, Tristan; Cooper, Ross; Yadavalli, Sailaja; Anderson, Kyle
ABSTRACT: Objectives : To assess the retear rate, retear size and location, the clinical impact of a retear, and preoperative patient factors related to postoperative outcome after arthroscopic suture bridge rotator cuff repair. Methods : Fifty six patients with an isolated, full-thickness supraspinatus tendon tear who underwent arthroscopic suture bridge rotator cuff repair were retrospectively identified. Patients were evaluated and rotator cuff integrity was assessed using ultrasonography. Visual analog score (VAS), the American Shoulder and Elbow Surgeon (ASES) score, shoulder range of motion and strength were used for clinical evaluation. Retears were assessed for size and location on ultrasonography. Results : Forty two patients (75%) aged a mean 59.7 ± 8.6 years (range 41–79 years) were available for follow-up at a mean 13.5 months. Postoperative evaluation indicated significant improvements in ASES score (49.76 ± 18.2 to 86.57 ± 13.4, P  < 0.001), VAS pain score (4.69 ± 2.17 to 0.63 ± 1.29, P  < 0.001), forward elevation range of motion (144.1° ± 29.9 to 159.69 ° ± 13.9, P  = 0.002), and internal rotation ROM (44.13° ± 12.0 to 52.09° ± 12.0, P =  0.003). The retear rate was 14.28% (6/42). Patients with retears were not older ( P  = 0.526) but had a larger preoperative tear size (3.25 cm ± 0.5 vs 2.05 cm ± 0.48, P  < 0.001). Preoperative tear size was significantly associated with a postoperative retear ( P  < 0.001). The duration of preoperative symptoms was significantly associated with pain ( P  = 0.029), pain improvement ( P  = 0.013), internal rotation ROM ( P  = 0.002), and internal rotation strength ( P  = 0.004). Conclusions : Arthroscopic suture bridge repair provides good clinical results with a low retear rate. The duration of preoperative symptoms was associated with postoperative outcome, indicating that delaying surgery may result in inferior outcomes. Level of Evidence : IV, Case Series